Analysis of the Impact of Gadgets on Student Learning Motivation on High School Chemistry Lessons - Rosanna, Desi Lisa (LAVOISIER: Chemistry Education Journal, 2023)
This study aims to determine the impact of using gadgets on high school students' learning motivation in high school chemistry lessons. The type of research used in this research is descriptive qualitative. Qualitative research is research that is intended to reveal symptoms as a whole and in accordance with the context or what they are through collecting data with a natural background as a direct source with the key research instruments themselves. So in this study the researchers conducted observations, interviews and documentation. The results of the study show that: 1) the use of gadgets among high school students, especially in chemistry lessons, is used as a communication aid in increasing student learning motivation such as the use of practicum videos and animations. But there are some students who often play games rather than study. 2) the positive impact of using gadgets, students are able to get information and communication easily while the negative impact of using gadgets during class hours can interfere with student learning concentration so that it can affect student learning behavior. Most students often open the internet and communicate for less useful things that can interfere with the learning process. So that it makes students' learning motivation decrease.